(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the diagnostic accuracy of urine dipstick in detection of UTI in children keeping urine culture as a gold standard. Study Design: Cross sectional validation study Place and Duration of Study: This study was conducted at the Paediatric department, KRL Hospital, Islamabad from July 2015 to December 2015. Materials and Methods: 406 female patients age 2 months to 5 years with signs and symptoms of urinary tract infection were included. Urine was collected using a midstream clean catch sample or suprapubic aspiration. A rapid dipstick analysis for leukocyte esterase and nitrite was done. All dipstick positive and dipstick negative samples underwent cultures by sending samples in a clean container to the pathology lab. A study proforma was used to record the information regarding patient age, gender and the results of urine dipstick and urine culture tests. Results: The diagnostic accuracy of urine dipstick in detection of UTI in children keeping urine culture as a gold standard was recorded as 80.95%, 62.42%, 35.98%, 92.63% and 66.26% for sensitivity, specificity, positive predictive value, negative predictive value and accuracy rate. Conclusion: The diagnostic accuracy of urine dipstick in detection of UTI in children keeping urine culture as a gold standard is higher and this cost effective technique may be used in our routine practice for early detection and treatment of UTI in children in order to avoid renal damage and when urine cultures are available only after 7 days.